Clinical Ethics on Film A Guide for Medical Educators - Rosenthal, M. Sara. (Cham : Springer International Publishing, 2018)
This book discusses feature films that enrich our understanding of doctor-patient dilemmas. The book comprises general clinical ethics themes and principles and is written in accessible language. Each theme is discussed and illuminated in chapters devoted to a particular film. Chapters start with a discussion of the film itself, which shares details behind the making of the film; box-office and critical reception; casting; and other facts about production. The chapter then situates the film in a history of medicine and medical sociology context before it delves into the clinical ethics issues in the film, and how to use it as a teaching aid for clinical ethics. Readers will understand how each film in this collection served to bring particular clinical ethics issues to the public's attention or reflected medico-legal issues that were part of the public discourse. The book is a perfect instructor's guide for anyone teaching bioethics, healthcare ethics, medical sociology, medical history, healthcare systems, narrative medicine, or nursing ethics.
Part 1: END OF LIFE ON FILM -- Chapter 1: If I Was Restricted to One Film: Wit (2001) -- Chapter 2: It's Really About Cruzan and Quinlan: Whose Life is It, Anyway? (1981) -- Chapter 3: Closure and Family Systems: My Life (1993) -- Chapter 4: "Bye, Bye, Life": All That Jazz (1979) -- Part 2: FILMS ABOUT COMPETENCY AND DECISION-MAKING CAPACITY -- Chapter 5: One Eye and an Alphabet: Diving Bell and the Butterfly (2007) -- Chapter 6: The Successful Delusional: K-PAX (2001) -- Chapter 7: Malingering and Nursing Ethics: One Flew Over the Cuckoo's Nest (1975) -- Chapter 8: Dementia and Capacity: Still Alice (2014) -- Part 3: FILMS ABOUT BENEFICENCE -- Chapter 9: "Am I Good Man, or a Bad Man?" The Elephant Man (1980) -- Chapter 10: Pediatric Ethics and the Limits of Parental Authority: Lorenzo's Oil (1992) -- Chapter 11: Weighing Clinical Goods over Clinical Harms: Awakenings (1990) -- Chapter 12: "She Threw Up in her Mask": The Verdict (1982) -- Chapter 13: "How Many Dead Hemophiliacs Do You Need?" And The Band Played On (1993) -- Chapter 14: The Tuskegee Syphilis Study: Miss Evers' Boys (1997) -- Chapter 15: Physician-Assisted Suicide: You Don't Know Jack (2010). -- Part 5: ORGANIZATIONAL ETHICS AND RESOURCE ALLOCATION -- Chapter 16: The U.S. Healthcare System: Sicko (2007) -- Chapter 17: We Heal No One; We Do Nothing: The Hospital (1971) -- Chapter 18: Some Good Parts: The Transplant Films -- PART 6: PROFESSIONALISM AND HUMANISM -- Chapter 19: A Classic for a Reason: The Doctor (1991) -- Chapter 20: A Home Healthcare Gem: Passion Fish (1992) -- Chapter 21: A Tale of Two Colleagues and Pediatric Surgery: Something the Lord Made (2004).
Religion and Philosophy
text file PDF
Keywords: Bioethics; Medical ethics; Communication; Social medicine; Medical laws and legislation